Transition-metal-free one-pot synthesis of alkynyl selenides from terminal alkynes under aerobic and sustainable conditions - Heredia, Adrián A.; Peñéñory, Alicia B. (Beilstein Journal of Organic Chemistry, 2017)
Alkynyl selenides were synthesized by a straightforward one-pot and three-step methodology, without the need of diselenides as starting reagents, under an oxygen atmosphere and using PEG 200 as the solvent. This procedure involves the in situ generation of dialkyl diselenides through a K3PO4-assisted reaction of an alkyl selenocyanate obtained by a nucleophilic substitution reaction between KSeCN and alkyl halides. Successive reaction with terminal alkynes in the presence of t-BuOK affords the corresponding alkyl alkynyl selenide in moderate to good yields. Finally, this methodology allowed the synthesis of 2-alkylselanyl-substituted benzofuran and indole derivatives starting from convenient 2-substituted acetylenes.
Keywords: alkynyl selenide; electrophilic cyclization; nucleophilic substitution; potassium selenocyanate; terminal alkynes

(untitled) - Mugesh, G.; du Mont, W.-W.; Sies, H. (Chem. Rev., 2001)

(untitled) - Nogueira, C. W.; Zeni, G.; Rocha, J. B. T. (Chem. Rev., 2004)

(untitled) - Chasteen, T. G.; Bentley, R. (Chem. Rev., 2003)

(untitled) - Morgenstern, R.; Cotgreave, I. A.; Engman, L. (Chem.-Biol. Interact., 1992)

(untitled) - May, S. W.; Wang, L.; Gill-Woznichak, M. M.; Browner, R. F.; Ogonowski, A. A.; Smith, J. B.; Pollock, S. H. (J. Pharmacol. Exp. Ther., 1997)

(untitled) - Diaz, P.; Gendre, F.; Bernardon, J.-M. (Tetrahedron Lett., 1998)

(untitled) - Bolzan, R. C.; Folmer, V.; Farina, M.; Zeni, G.; Nogueira, C. W.; Rocha, J. B. T.; Emanuelli, T. (Basic Clin. Pharmacol. Toxicol., 2002)

Modern Alkyne Chemistry. Catalytic and Atom-Economic Transformations - Trost, B. M.; Li, C. J. (Wiley-VCH Verlag GmbH & Co, 2014)

Acetylene Chemistry: Chemistry, Biology and Material Science - Diederich, F.; Stang, P. J.; Tykwinski, R. R. (Wiley-VCH, 2005)

The Chemistry of Organic Selenium and Tellurium Compounds - Rappoport, Z. (Wiley and Sons, 2014)

(untitled) - Alonso, F.; Beletskaya, I. P.; Yus, M. (Chem. Rev., 2004)

(untitled) - Yang, D. Y.; Huang, X. (J. Organomet. Chem., 1997)

(untitled) - Huang, X.; Ma, Y. (Synthesis, 1997)

(untitled) - Dabdoub, M. J.; Begnini, M. L.; Guerrero, P. G., Jr (Tetrahedron, 1998)

(untitled) - Sun, A.; Huang, X. (Synthesis, 2000)

(untitled) - Comasseto, J. V.; Menezes, P. H.; Stefani, H. A.; Zeni, G.; Braga, A. L. (Tetrahedron, 1996)

(untitled) - Tiecco, M.; Testaferri, L.; Temperini, A.; Bagnoli, L.; Marini, F.; Santi, C.; Terlizzi, R. (Eur. J. Org. Chem., 2004)

(untitled) - Godoi, B.; Schumacher, R. F.; Zeni, G. (Chem. Rev., 2011)

(untitled) - Gabriele, B.; Mancuso, R.; Larock, R. C. (Curr. Org. Chem., 2014)

(untitled) - Manarin, F.; Roehrs, J. A.; Gay, R. M.; Brandão, R.; Menezes, P. H.; Nogueira, C. W.; Zeni, G. (J. Org. Chem., 2009)

(untitled) - Godoi, B.; Speranca, A.; Back, D. F.; Brandao, R.; Nogueira, C. W.; Zeni, G. (J. Org. Chem., 2009)

(untitled) - Stein, A. L.; Bilheri, F. N.; Zeni, G. (Chem. Commun., 2015)

(untitled) - Cook, D. J.; Hill, A. F.; Wilson, D. J. (J. Chem. Soc., Dalton Trans., 1998)

(untitled) - Das, J. P.; Roy, U. K.; Roy, S. (Organometallics, 2005)

(untitled) - Dahdoub, M. J.; Comasseto, J. V.; Braga, A. L. (Synth. Commun., 1988)

(untitled) - Braga, A. L.; Reckziegel, A.; Menezes, P. H.; Stefani, H. A. (Tetrahedron Lett., 1993)

(untitled) - Kundu, A.; Roy, S. (Organometallics, 2000)

(untitled) - Sharma, A.; Schwab, R. S.; Braga, A. L.; Barcellos, T.; Paixão, M. W. (Tetrahedron Lett., 2008)

(untitled) - Ahammed, S.; Bhadra, S.; Kundu, D.; Sreedhar, B.; Ranu, B. C. (Tetrahedron, 2012)

(untitled) - Bieber, L. W.; da Silva, M. F.; Menezes, P. H. (Tetrahedron Lett., 2004)

(untitled) - Mohammadi, E.; Movassagh, B. (Tetrahedron Lett., 2014)

(untitled) - Godoi, M.; Ricardo, E. W.; Frizon, T. E.; Rocha, M. S. T.; Singh, D.; Paixão, M. W.; Braga, A. L. (Tetrahedron, 2012)

(untitled) - Mohan, B.; Hwang, S.; Woo, H.; Park, K. H. (Synthesis, 2015)

(untitled) - Godoi, M.; Liz, D. G.; Ricardo, E. W.; Rocha, M. S. T.; Azeredo, J. B.; Braga, A. L. (Tetrahedron, 2014)

(untitled) - Mohan, B.; Park, J. C.; Park, K. H. (ChemCatChem, 2016)

(untitled) - Rampon, D. S.; Giovenardi, R.; Silva, T. L.; Rambo, R. S.; Merlo, A. A.; Schneider, P. H. (Eur. J. Org. Chem., 2011)

(untitled) - Movassagh, B.; Navidi, M. (Chin. Chem. Lett., 2012)

(untitled) - Heredia, A. A.; Peñéñory, A. B. (RSC Adv., 2015)

Alternative Solvents for Green Chemistry. Liquid Polymers - Kerton, F.; Marriott, R. (Royal Society of Chemistry, 2009)

(untitled) - Perin, G.; Borges, E. L.; Alves, D. (Tetrahedron Lett., 2012)

(untitled) - Michel, P.; Gennet, D.; Rassat, A. (Tetrahedron Lett., 1999)

(untitled) - Hijfte, L. V.; Kolb, M.; Witz, P. (Tetrahedron Lett., 1989)

(untitled) - Turrens, J. F. (J. Physiol., 2003)

(untitled) - Kumar, A.; Bhakuni, B. S.; Prasad, C. D.; Kumar, S.; Kumar, S. (Tetrahedron, 2013)

(untitled) - Xu, X.-H.; Lu, R. L.; Zhang, Q.-L.; Chen, X.; Li, Y.-J.; Zhang, Q.-L. (Gaodeng Xuexiao Huaxue Xuebao, 2005)

(untitled) - Feula, A.; Fossey, J. S. (RSC Adv., 2013)

(untitled) - Nouri-Nigjeh, E.; Permentier, H. P.; Bischoff, R.; Bruins, A. P. (Anal. Chem., 2010)

(untitled) - Shaw, S.; Jayatilleke, E.; Herbert, V.; Colman, N. (Biochem. J., 1989)

(untitled) - Vázquez-Vivar, J.; Whitsett, J.; Martásek, P.; Hogg, N.; Kalyanaraman, B. (Free Radical Biol. Med., 2001)

(untitled) - Koradin, C.; Dohle, W.; Rodriguez, A. L.; Schmid, B.; Knochel, P. (Tetrahedron, 2003)